PENGARUH CORPORATE SOCIAL RESPONSIBILITY, STRUKTUR MODAL, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN: PROFITABILITAS SEBAGAI VARIABEL MODERATING (studi kasus pada perusahaan manufaktur yang terdaftar di BEI periode 2015-2017) - Hafiana Farah Diana Putri; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis research is conducted to examine the effect of Corporate Social Responsibility, Capital Structure and Liquidity of Company Values: Profitability as a Moderating Variable. The population that is used in this research are manufacturing companies which is listed in the Indonesia Stock Exchange on 2015-2017. The method that is utilized in this research is the multiple linear regression analysis. In addition, the absolute residual is used for the moderating variable by using IBM SPSS Statistic 20. The results of sampling are produced by engaging the Purposive sampling and resulting in the amount of 28 Manufacturing companies which compiled the sample criteria.Based on the hypothesis testing results that is carried out, the conclusion drawn from the research are; the Corporate Social Responsibility affects significantly in a negatife way towards the company values, Capital Structure (DER) affects insignificantly towards the company values, Profitability is able to moderate the relationship between CSR and the company values whereas Profitability is unable to moderate the relationship between capital structure (DER) and Liquidity (CR) towards company values.Keywords: Corporate Social Responsibility, Capital Structure, Liquidity, Company Values and Profitability.